2018
DOI: 10.1186/s13058-018-0992-0
|View full text |Cite
|
Sign up to set email alerts
|

ETV4 transcription factor and MMP13 metalloprotease are interplaying actors of breast tumorigenesis

Abstract: BackgroundThe ETS transcription factor ETV4 is involved in the main steps of organogenesis and is also a significant mediator of tumorigenesis and metastasis, such as in breast cancer. Indeed, ETV4 is overexpressed in breast tumors and is associated with distant metastasis and poor prognosis. However, the cellular and molecular events regulated by this factor are still misunderstood. In mammary epithelial cells, ETV4 controls the expression of many genes, MMP13 among them. The aim of this study was to understa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(43 citation statements)
references
References 53 publications
4
37
0
Order By: Relevance
“…Furthermore, ETV4 could regulated the P3H4 transcription in EJ and T24 cells. ETV4 (ETS Variant 4) is a transcription factor belonging to the EST family and is specifically involved in the carcinogenesis of various tissues, including pancreatic cancer, breast cancer and intestinal cancer [24][25][26]. However, little is known about the role of ETV4 in BC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, ETV4 could regulated the P3H4 transcription in EJ and T24 cells. ETV4 (ETS Variant 4) is a transcription factor belonging to the EST family and is specifically involved in the carcinogenesis of various tissues, including pancreatic cancer, breast cancer and intestinal cancer [24][25][26]. However, little is known about the role of ETV4 in BC.…”
Section: Discussionmentioning
confidence: 99%
“…In pancreatic cancer and breast cancer, ETV4 directly upregulates the transcription of cyclin proteins, such as cyclin D1 [26] and cyclin D3 [29] to promote cell proliferation. MMPs, such as MMP13 and urokinase plasminogen activator (uPA) are also transcriptionally regulated by ETV4, which are involved in the ETV4-driven malignant phenotypes in prostate cancer [30] and breast cancer [25].…”
Section: Discussionmentioning
confidence: 99%
“…Collagen degradation is necessary for tumor invasion, and matrix metalloproteinases, which play important roles in this process, have direct causative effects on tumor progression (Page-McCaw et al, 2007;Hoffman et al, 2011;Torzilli et al, 2012). The hub gene matrix metalloproteinase 13 promotes the progression of different kinds of cancers (Dumortier et al, 2018;Liu et al, 2018). Therefore, these hub genes may promote the progression of ETE in PTC through direct or indirect interactions.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the prognosis of CCA patients urgently requires to be improved. A number of studies have reported that certain molecular biomarkers have crucial roles in tumor pathogenesis and development, and are highly associated with the prognosis for human malignant disease (19)(20)(21). Various prognostic biomarkers have also been identified in CCA.…”
Section: Discussionmentioning
confidence: 99%